FREE WILL AS READERS' RESPONSES TO STEPHENIE MEYER'S NOVEL: TWILIGHT - Mirna Tania, - (2011)
The present study attempts to disclose 1) Readers' perspectives on human free will as reflected through the main character, Bella, in Twilight; and 2) the processes of response as evidenced from readers' responses. To investigate the issues, the writer used qualitative approach by applying a case study. The data are 14 readers' written responses. The writer also conducted interviews with the 14 readers to validate the readers' written responses. Using the framework developed by Rosenblatt (1993), the results of the study indicate that the readers' responses to Twilight showed three groups of human free will issues, namely: (1) Human free will group (a human has free will and a human has and hasn't free will), (2) Internal conflict group (avoidance and desire conflict), and (3) Moral responsibility group (causal responsibility, responsibility caused by other subjects, responsibility as obligation and responsibility as a choice). The obtained data show Beach's specific processes of response (1993). It found that the most frequently processes of response used engaging with 131 items (41.5%), followed by constructing with 69 items (21.8%), imaging with 51 items (16.2%), reflecting/evaluating with 39 items (12.3%), and connecting with 26 items (8.2%). This study suggests that there is a close relation between readers' perspectives on human free will, internal conflict, and moral responsibility and their culture, age, and beliefs. The readers' processes of response indicate that past experiences, thoughts, ideas from the readers, past readings and present personality affect their perspective on the human free will issues.